Introduction to occupational health workbook - Rasdi, Irniza; Darus, Azlan (Universiti Putra Malaysia Press, 2019)
This book contains 14 important chapters related to OSH including introduction, legislation provision, five different occupational main hazards, medical surveillance and work compensation. Each chapter consists of questions that will guide users in their self-learning on the essentials of basic concepts of OSH. Questions provided are designed to stimulate and encourage critical thinking process for comprehensive and efficient self-learning. Users are encouraged to discuss their answers with those who are experts in occupational safety and health to avoid misinterpretation or incorrect information.